War, Peace and Private Portfolios. - Collier, P; Gunning, J (1995)
During civil wars trading is profitable as markets fragment. Profits may be saved in old form, because investment is too risky. In a successful economic transition to peace these liquid assets are switched into investment. Continuing fears of insecurity, however, may keep portfolios liquid. We consider three policy consequences. The unpredictable return of confidence causes erratic changes in the demand for money, complicating monetary targeting. Government liabilities become unmarketable except at prohibitive interest rates, though the state may be able to sell real assets. The government can subsidize the act of investment commitment by temporarily undervaluing the exchange rate.